English Language Teachers’ Professional Identity: A Review - Deuja, Ramita (Tejganga Darpan, 2024)
This paper reviews ten peer-reviewed empirical research studies on English language teachers’ identity construction from 2018 to 2022.The review study follows a systematic process of paper selection and analysis. The result of the study is presented in two major themes: contextually situated English language teachers’ identity and English language teachers’ identity formation process. Similarly, the paper also critically presents the review of the methodology adopted in identity research. The findings of the study shed light on contextual factors, which are heavily influential in language learning process. Besides, this review study presented the identity formation process of EFL teachers in five different stages. The study concludes that the identity construction process begins from pre-service learning to a career-long process.